STRATEGI PENINGKATAN KINERJA KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU SENAPELAN - Elang Muhamad Kusuma; Zulkarnain Zulkarnain; Samsir Samsir (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2023)
The purpose of this research is to analyze the competency of the resources owned by the Pekanbaru Senapelan Pratama Tax Service Office in implementing the strategic management model of the resource-based view. The capability of the Pekanbaru Senapelan Primary Tax Service Office in implementing strategic management model resource-based view. The strategy used by the Pekanbaru Senapelan Pratama Tax Service Office in implementing the resource-based view strategic management model. Based on the data obtained from the Senapelan Pekanbaru Primary Tax Service Office, it is known that the number of employees who are also the population in this study is 102 people. The data used in this study are primary data and secondary data, while the data collection technique uses a questionnaire. The data analysis technique used in this study is the data analysis used in this study is SWOT. The results of the study show that the resource competence of the Pekanbaru Senapelan Pratama Tax Service Office shows a strong position, meaning that the organization has DGT apparatus resources which are dominated by employees with strong technical competence, which includes service functions, supervision and law enforcement. Then the capability possessed by the Pekanbaru Senapelan Pratama Tax Service Office is included in the strong category. The Pekanbaru Senapelan Pratama Tax Service Office strategy that has been implemented so far shows a strong category and the position of the Pekanbaru Senapelan Primary Tax Service Office is in quadrant V position. In quadrant V, the most using both hold and guard strategies. This position indicates that the Pekanbaru Senapelan Primary Tax Service Office is in a defensive position and maintains that internal environmental conditions remain in a position to maximize strengths and minimize weaknesses by taking advantage of existing opportunities and preventing external threats. In this position the most appropriate strategy is market penetration and product development strategy. Keywords: Application of Strategic Management Model Resource Based View, SWOT